Alterações na produtividade do milho, desempenho animal e lucratividade de sistemas integrados pela presença de árvores, doses de nitrogênio e estratégia de adubação - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
There is growing social and political pressure in favor of the conservation of natural ecosystems, in parallel with the increase in urbanization. Consequently, consumption of plant and animal raw materials is expected to increase, stimulating, at the same time, the intensification of land use. Among the practices that can contribute to such intensification occurring in a sustainable manner, the most notable are integrated agricultural production systems (ICLS), the adoption of the direct planting system (SPD) and the use of system fertilization linked to nutrient cycling. One of the benefits of such practices is the reduction in dependence on external inputs. In ICLS, when using phosphorus (P) and potassium (K) as a fertilization strategy during winter pasture periods, they do not compromise grain production in the summer. However, few studies consider this NPK fertilization strategy in corn and in different ICLS. The objective of the present study was to analyze the effect of the presence of Eucalyptus grandis trees, two doses of nitrogen fertilization in winter pasture and system fertilization on corn grain productivity, animal performance, in the agricultural year 2022/2023, and the profitability of different ICLS. The present study was conducted at the Fazenda Modelo Research Station of the Rural Development Institute of Paraná IAPAR-Emater (IDR - Paraná). The area was divided into 12 experimental units, six of which were wooded. The experimental design was randomized blocks, with three replications, in a 2 x 2 factorial arrangement in winter, that is, two doses of N (50 and 150 kg N ha-1 , applied as cover in the pasture) and two systems (CL, crop-livestock only x CLT, crop-livestock with trees). The winter pasture was composed of black oat (IPR 61) + ryegrass (BRS Ponteio). Grazing was carried out by Purunã breed heifers, with an initial average age of 15 months, using the continuous stocking method with variable stocking rate to maintain the average pasture height of around 25 cm. In the corn crop phase (hybrid 2401 PWU), subplots were implemented in each experimental unit to evaluate without vs. with 350 kg ha-1 of NPK (10-20-20, i.e., 35 kg N ha-1 , 70 kg P2O5 ha-1 and 70 kg K2O ha- 1 ) as base fertilizer and in sub-subplots two doses of nitrogen fertilizer (0 and 150 kg N ha- 1 in coverage). No significant differences were observed between the factors studied for pasture height (24.4 ± 0.64 cm) and for average daily gain (0.843 ± 0.04 kg/animal/day). Significant differences (P>0.05) between systems were observed in stocking rate (905 ± 72.3 kg LW ha-1 in the CL and 710 ± 61.1 kg LW ha-1 in the CLT system) and in live weight gain (LW) per area, with the CLT presenting 3.8 ± 0.4 kg of LW ha-1 day-1 and the CLT 3.0 kg of LW ha-1 day-1 . Significant differences between nitrogen doses were observed for the total LW gain per area, being higher (403.6 ± 23.7 kg LW ha-1 ) at a dose of 150 kg N ha-1 than at a dose of 50 kg N ha-1 (283.6 ± 26.6 kg LW ha-1 ), in 94 days of grazing. The CLT had a higher proportion of leaves (26.3 ± 1.5% of leaves) than the CL (23.53 ± 2.1% of leaves). No response was observed in terms of corn productivity to the increase in N dose in the pasture phase and subsequent nitrogen fertilization in top dressing in the corn cultivation phase. A significant interaction between systems and base fertilizer was observed, with higher production values in the CL with base fertilizer (10050 kg ha-1 ), without significant differences between the other treatments (7504 kg ha-1 ). The delay in sowing corn may have influenced these results. Regarding economic analysis, the most profitable treatment (US$ 152 ± 125,8 ha-1 ) was CL with a dose of 350 kg of NPK as base fertilizer on corn. In the present study, shading and/or competition with trees for water and nutrients, combined with the rapid growth of eucalyptus, directly impacted productivity and final profit, as the CLT system presented losses in this agricultural year, ranging between US$ -292 ± 84.9 ha-1 (without NPK) e US$ -524 ± 59,3 ha-1 (with NPK). The highest doses of N (i.e., 150 kg ha-1 ) used did not result in greater profit and productivity, both in pasture and in corn coverage. Therefore, the challenge is to balance competition between trees and associated crops in the CLT system, ensuring sustainable levels of yield.
Keywords: Agricultura sustentável; Integração Lavoura-Pecuária-Floresta; Integração Lavoura-Pecuária; Rentabilidade; Eucalyptus grandis; Sustainable Agriculture; Integrated Crop-Livestock-Forest system; Integrated Crop-Livestock system; Profitability; Eucalyptus grandis; CNPQ::CIENCIAS AGRARIAS::ZOOTECNIA